Analysis of Quality and Cognitive Levels of Physics Final Assessment Questions of Class X - Agustina Trianti Br Sinaga; Rosane Medriati; Eko Risdianto (IJOEM: Indonesian Journal of E-learning and Multimedia, 2023)
This study aims to describe the quality and distribution of cognitive levels of physics final assessment questions for class X. This research is a quantitative descriptive study. The research subjects were in the form of student questions and answer sheets at Senior High Schools 4, 8, and 9 Bengkulu City. The results showed that Senior High School 4 had 64% good questions, 12% good enough, 24% bad, and cognitive levels C1 (4%), C2 (20%), C3 (68%), C4 (8%), there is neither C5 nor C6. Senior High School 8 has 21% good questions, 11% good enough, and 68% bad questions, as well as cognitive levels C1 (3%), C2 (13%), C3 (55%), C4 (29%), and not there are C5 and C6. Senior High School 9 has 7% good questions, 29% good enough, 64% bad questions, and cognitive levels C1 (11%), C2 (21%), C3 (68%), and no C4, C5 or C6.